Analysis Of The Suitability Of INA-CGBS Claim Coding at BPJS Kesehatan Wasin at RSUP prof. dr. I.G.N.G.NGOERAH Denpasar - Sutrisnawati, Gusti Ayu Eka; Manuaba, Fajar; Purwani, Sagung Putri M.E (Jurnal Health Sains, 2023)
RSUP Prof.Dr.I.G.N.G.Ngoerah Denpasar is an advanced service facility which is part of supporting the running of national insurance programs processed by the BPJS agency. The BPJS Health wasin audit aims to ensure that companies or participants have fulfilled their obligations regarding health insurance provided by BPJS Health, where reimbursement for advanced health services costs uses the INA-CGBs E-Claim application. INA-CBG E-Claim is an application specifically designed to assist hospitals in the national health insurance claim process. INA-CBG's is the amount of claim payment by BPJS to health facilities where the INA-CBG's rate uses a coding system with ICD-10 for diagnosis and ICD 9CM for procedures or actions. The aim of this research is to obtain the suitability of INA-CBGs claim coding on BPJS Health wasin at Prof. Dr. IGNGNgoerah Denpasar Hospital. Empirical legal research used in this research, with a quantitative approach. which exists in fact. The results of this research are that the impact of losses from discrepancies in the coding of clinical data affects the financing of health services, so there is a need for a BPJS Health data processing process regarding re-confirmation regarding the advantages and disadvantages of claims that will be paid. In August 2023, there was confirmation that there were 638 inpatient data processing data, 2339 outpatient data. Then action was taken by the hospital to provide training to coding officers and continue to regularly monitor and check the hospital's internal verification.